A co-opetitive framework for the hub location problems in transportation networks. (2nd December 2017) - Neamatian Monemi, Rahimeh; Gelareh, Shahin; Hanafi, Saïd; Maculan, Nelson
Abstract : In this paper, we present the first model of co-opetition for a Hub Location Problem between two logistics service provider (LSPs) companies where the mother company is the owner of infrastructure. The LSPs would like to cooperate with each other by establishing joint edges with limited capacities connecting their service networks. Such services are in form of pendulum services (a direct service between two points) between nodes of different networks. Additional market can be generated as a result of joining the two networks. At the same time, a competition is taking place between the two operators to increase their share from the additional market generated. In order to solve this problem, we propose a matheuristic approach combining a local search algorithm and a Lagrangian relaxation-based approach. In our matheuristic algorithm, the neighbourhood solutions are evaluated using a Lagrangian relaxation-based approach. Numerical results of applying the proposed algorithm on a real case study of the problem are presented.